2014
DOI: 10.1155/2014/438176
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Hydraulic Performance in Permanent Maglev Pump for Water-Jet Propulsion

Abstract: The operation of water-jet propulsion can generate nonuniform inflow that may be detrimental to the performance of the water-jets. To reduce disadvantages of the nonuniform inflow, a rim-driven water-jet propulsion was designed depending on the technology of passive magnetic levitation. Insufficient understanding of large performance deviations between the normal water-jets (shaft) and permanent maglev water-jets (shaftless) is a major problem in this paper. CFD was directly adopted in the feasibility and supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…According to previous research [29][30][31], non-uniform inflow conditions of waterjet pumps exhibit four distinct vortex structures: concentrated separation vortex (CSV), circumferential vortex (CV), hub spanwise vortex (HSV), and flow separation. To investigate the relationship between these vortex structures and pump performance, four modalities were utilized as boundary conditions in the subsequent CFD calculation for further study of flow field analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous research [29][30][31], non-uniform inflow conditions of waterjet pumps exhibit four distinct vortex structures: concentrated separation vortex (CSV), circumferential vortex (CV), hub spanwise vortex (HSV), and flow separation. To investigate the relationship between these vortex structures and pump performance, four modalities were utilized as boundary conditions in the subsequent CFD calculation for further study of flow field analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that the semi-submersible non-axial current generator [8] designed in this project is applied to the coastal scene where the current velocity is 1-2 m/s, the above simulation results show that after the airfoil deflector accelerates 1 m/s and 2 m/s ocean currents, the average current velocity through the non-axial current generator's non-axial rim is 2.02 m/s and 4.1 m/s respectively. By referring to relevant literature, it is obtained that the generator power coefficient Cp is 0.31, Șe is the generator efficiency is 0.9, ȡ is the density of seawater, which is 1.05 × 10 ଷ ݇݃/݉ ଷ .…”
Section: Power Calculation Of Semi-submersible Shaftless Ocean Curren...mentioning
confidence: 99%
“…In recent years, many studies have confirmed that numerical simulations can accurately predict performances of a water-jet pump and a complete water-jet propulsion system. 7,8,10 In this article, the commercial software ANSYS-CFX is used to simulate the threedimensional (3D) flow within a complete water-jet propulsion system, where the pump suction flow is non-uniform. Meanwhile, the steady simulation of a single water-jet pump is also performed to obtain performances under the uniform suction flow.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The boundary layer thickness was calculated by Wieghardt equation. 10,12 All the physical walls were set as nonslip walls…”
Section: Geometry Of the Water-jet Pumpmentioning
confidence: 99%